2023
DOI: 10.1108/ijhma-01-2022-0013
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between macroeconomic variables on residential property price: case study in Malaysia before and during COVID-19

Abstract: Purpose The purpose of this study is to analyse numerous aspects affecting residential property price in Malaysia against macroeconomics issues such as gross domestic product (GDP), exchange rate, unemployment and wage. Design/methodology/approach The hedonic pricing model has been adopted as econometric model for this research to investigate the relationship between residential property price against macroeconomics indicator. The data for residential property price and macroeconomic variables were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The Malaysian Ministry of Higher Education has allocated RM 1000 billion to enhance the employability of graduates in the post-COVID-19 era [32,33]. The findings of this research will provide a clear picture of the efficacy of the programmes implemented to increase the marketability of graduates and can be utilised by the government in the development of intervention plans to enhance the marketability of graduates.…”
Section: Implications Of the Studymentioning
confidence: 92%
“…The Malaysian Ministry of Higher Education has allocated RM 1000 billion to enhance the employability of graduates in the post-COVID-19 era [32,33]. The findings of this research will provide a clear picture of the efficacy of the programmes implemented to increase the marketability of graduates and can be utilised by the government in the development of intervention plans to enhance the marketability of graduates.…”
Section: Implications Of the Studymentioning
confidence: 92%
“…At the same time, a study by Kanwal and Nadeem (2013) found that higher GDP is linked with better company performance, especially the return on assets (ROA). A study by Zulkarnain and Nawi (2023) also showed that GDP strongly correlates with house price increases. However, Olalere et al (2021) argued that the GDP rate had an insignificant impact on firm value.…”
Section: Key Macroeconomic Factor On Firm Valuementioning
confidence: 92%
“…Initially, correlations were assumed to be constant, and researchers and practitioners estimated a single estimate of the coefficient for the period, and it was implicit in this that this relationship stayed constant over time. Following that, researchers realised that the relationships among economic variables change over time (see, for example, Bekaert and Harvey 1995;Zulkarnain and Nawi 2023;Sadiq et al 2023). To incorporate these changes, researchers began using a moving window of time to estimate correlations (see, for example, Jeon and McCurdy 2017).…”
Section: Time Varying Correlationsmentioning
confidence: 99%